Optimizing Health Educated Family to Reduce Hypertension and Integrated Diabetes Mellitus in Bligo - Hanna Rasyidah; Halim Purnomo; Nada Nadiva Aisy Amieni; Naura Ufaira; Naufal Raihan Ramadhan; Lia Fakila Nisa; Zalfaa Hanifatun Nisa; Amri Adi Nur Salam; Dipo Andang Narpati; Dyah Raras Anindhita; Ersan Al-Ghazali; Hiban Qosthori; Marsya Nadiyyatul Hani’ah; Muhammad Imam Mahfudz; Mullah Muhammad Agwa; Nurfiana Nurfiana; Sajida Fihrisa Afaki; Sri Riyani; Tri Wahyuningsih (Universitas Alma Ata, 2024)
The Community Service Program (KKN) conducted in Bligo Village, Buaran District, Pekalongan Regency, aimed to optimize the Family Guidance program in reducing hypertension and diabetes mellitus rates. The program included various activities such as health education, screening, and family guidance for high-risk individuals. The results showed a decrease in blood pressure and blood sugar levels among participants, accompanied by lifestyle changes towards healthier habits. The success of this program highlights the importance of active community participation and support from various stakeholders in addressing non-communicable health issues within the community